FAMILY FANNIIDAE - Grisales, Diana; de Carvalho, Claudio J. B. (Zootaxa, 2016)
Here we catalogue 32 species in two genera of Fanniidae (Euryomma and Fannia) from Colombia and provide geographical information for all species, when available.